EXPLICIT PLANNING FOR PARAGRAPH WRITING CLASS - Setyowati, Lestari; El-Sulukiyyah, Ana Ahsana (Jurnal Bahasa Lingua Scientia, 2017)
The purpose of the study is to improve the students writing ability for paragraph writing class. The subjects of the study were 37 students of English Education Study Program who joined the paragraph writing class. The design of the study was Classroom Action Research with two cycles. Cycle 1 consisted of three meetings, and cycle 2 consisted of two meetings. The types of explicit planning used in the action research were word listing and word mapping with phrases and sentence for detail.  The instruments used were direct writing test, observation, and  documentation of students’ reflective essay. To score the students’ writing, two raters  were asked to rate the composition by using Jacobs ESL Composition profile scoring rubric. The finding shows that the use of explicit planning was able to improve the students’ paragraph writing performance, indicated with the achievement of the criteria of success. The students’ mean improved from cycle 1 (74.62)  to cycle2 (76.78). Although explicit planning instruction was able to help the students to write better, data from their self-reflection essay showed that many of the students preferred to use free writing instead of explicit planning instruction.